A spectroscopic study for the pH-effect on the thermodynamics of formation for colored Azo-dyes prepared from the reaction of paracetamol with two diazotized reagents - Ammar Y. Hashim; Dr.Mohammad Mahmoud Hussein Al-Niemi (College of Education for Pure Sciences, 2023)
This research included a spectroscopic study of the effect of the pH function on the thermodynamics of the formation of the two colored Azo-dyes prepared from the interaction of paracetamol with two different diazotized reagents at three acidic media: acidic, neutral and basic, at a constant temperature (288K). The optimal conditions for each prepared Azo-dye were studied with meta-aminophenol and para-aminobenzoic acid, as well as the optimal ratios for its components, which were (1:1) for (Drug:Reagent).The stability constants of the two prepared Azo-dyes were found at the three pH and at the five temperatures (283, 293, 303, 313 and 323K). Then we studied the factors that affect the values of its stability constants, namely:Firstiy- The effect of the pH function: We found the stability constants for each of the Azo-dyes prepared at each pH and different temperatures, which are evidence for the preparation of stable Azo-dyes.Secondly- The effect of temperature: We calculated these stability constants at the aforementioned five temperatures, which allowed us to know that the reactions of formation of Azo-dyes are spontaneous and exothermic of negative values of (G and H) respectively, as well as a negative value of (∆S) that supports what has been mentioned previously.Thirdly- Effect of Structure: Finally, the structural formula of the diazotized reagent has an effect on the values of the stability constants for the formation of the prepared Azo-dyes, and this has been proven through the variation in the values of the stability constants.